A COMPARATIVE STUDY ON THE PERFORMANCE OF VARIOUS POVERTY - DINESH KUMAR (International Journal of Multidisciplinary Research and Studies, 2020)
One of the most difficult goals of economic growth in the 21st century has been to reduce global poverty while simultaneously enhancing the general welfare of people everywhere Among the worldwide concerns that are coming into the image of today's economy are issues such as widespread poverty, widespread starvation, widespread illiteracy, and widespread social difficulties. Every state has its own distinct problems with poverty, and every state devises its own unique remedies to the problem, taking into account the specific poverty indicators and causes that are unique to each state. Thus, it is quite intriguing to investigate the strategies and policies that are being implemented to fight poverty as well as the path ahead that each nation has chosen to pursue.